Experimental investigation of heat transfer and friction factor of TiO2-SiO2 nanofluids in water:ethylene glycol mixture - M. F., Nabil; Azmi, W. H.; Abdul Hamid, K.; R., Mamat (Elsevier, 2018)
This paper introduces the combination of two different nanoparticles suspended in the base ﬂuid for the enhancement of forced convection heat transfer. The aims of the experimen tal study are to investigate the heat transfer performance and friction factor of TiO 2-SiO 2 nanoﬂuids in a circular tube under turbulent ﬂow. The TiO 2-SiO 2 nanoﬂuids are prepared by using the two-step method for 0.5 to 3.0% volume concentration with nanop article mixture ratio of 50:50. The TiO 2-SiO 2 nanoparticles are dispersed in a base ﬂuid of water/E G mixture with a 60:40 volume ratio. The forced convection heat transfer experiment is conducted under working temperatures of 30, 50 and 70C and a constant heat ﬂux boundary condition. The heat transfer coefﬁcient of TiO 2-SiO 2 nanoﬂuids is enhanced with increase of volume concentration and temperature. It was observed that the maximum enhancement of convective heat transfer is 81% higher than the base ﬂuid for a volume concentration and temperature of 3.0% and 70C, respectively. Furthermore, the friction factor of TiO 2-SiO 2 nanoﬂuids is slightly increased with volume concentration,however insigniﬁcantl y. Finally, the regressi on correlation model of TiO2 -SiO 2 nanoﬂuids was developed from the experimental results for the estimation of Nusselt number and friction factor.